Differential effects of hydrocortisone on aspartate aminotransferase isoenzymes of the liver of rats during growth, development, and senescence - Patnaik S.K.; Sharma R.; Patnaik R. (My University, 2025)
The activity and induction patterns of the isoenzymes of aspartate aminotransferase (AsAT) of the liver of male rats during growth, development, and senescence were studied. The activity of both the cytoplasmic and mitochondrial isoenzymes increased significantly until adulthood and remained constant thereafter. Adrenalectomy decreased, and hydrocortisone administration increased, the activity of the cytoplasmic AsAT of the liver of young-immature, adult, and senescent rats. However, the degree of these responses decreased with increasing age of the animal. The hormone-mediated induction of this isoenzyme is actinomycin D-sensitive. Mitochondrial AsAT on the other hand is irresponsive towards these treatments throughout the life span of the rat.